Development of an IoT-Based Chicken Manure Management System Prototype for Efficiency and Sustainability - Bambang; Henry Simanjuntak; Akni Widyastuti; Panji P; Kurniawan Saputra; Tri Sandhika Jaya (Jurnal Informatika dan Rekayasa Perangkat Lunak, 2025)
Increasing the production scale of laying hen farms results in significant manure waste, thus posing challenges to animal and human health, as well as environmental quality. To address these issues, this study aims to develop a prototype of an Internet of Things (IoT)-based multilevel manure management system to improve operational efficiency and support farm sustainability. The study used a method that included needs analysis, design, implementation, and testing with a blackbox testing approach. The system was designed using the DS3231 RTC module for automatic scheduling, the MQ2 sensor for air quality detection, the ESP8266 microcontroller as the control center, the BTS7960 driver as the current regulator, and the DC motor and conveyor as actuators that drive manure removal, with monitoring results displayed on the LCD. The test results showed that all components functioned as designed: the RTC was able to execute the schedule on time, the MQ2 sensor detected the gas threshold accurately, the ESP8266 processed data and sent instructions properly, the BTS7960 delivered a stable current, the DC motor and conveyor worked according to the set duration. This study provides practical implications for modern farm management through the application of the environmentally friendly smart farming concept.